Tocolysis with the β2-sympathomimetic fenoterol does not increase the occurrence of infantile hemangioma in preterm and term infants - Hudalla, Hannes; Karmen, Christian; Bruckner, Thomas; Wallwiener, Stephanie; Fluhr, Herbert; Freis, Alexander; Strowitzki, Thomas; Pöschl, Johannes; Kuon, Ruben-Jeremias (Archives of gynecology and obstetrics, 2018)
Purposeβ2-sympathomimetics are used in obstetrics as tocolytic agents, despite a remarkable profile of side effects. Recently, the β2-sympathomimetic tocolytic drug hexoprenaline was identified as an independent risk factor for the development of infantile hemangioma (IH) in preterm infants. The aim of this study was to evaluate whether this observed effect was applicable to other β2-mimetic tocolytic agents like fenoterol.MethodsClinical prospectively collected data of all infants born between 2001 and 2012 and admitted to the neonatal intensive care unit (NICU) at Heidelberg University Hospital and respective maternal data were merged. For the current retrospective cohort study, cases (IH) were matched to controls (no IH) at a ratio of 1:4, adjusting for birth weight, gestational age, gender and multiple gestations. Prenatal exposure to fenoterol and perinatal outcome were analyzed in the total cohort and in subgroups.ResultsN = 5070 infants were admitted to our neonatal department, out of which n = 172 infants with IH were identified and compared to n = 596 matched controls. Exposure to fenoterol was not associated with a higher rate of IH in the total matched population (OR 0.926, 95% CI 0.619-1.384) or in a subgroup of neonates < 32 weeks of gestation or with a birth weight < 1500 g (OR 1.127, 95% CI 0.709-1.791). In the total matched population, prenatal exposure to glucocorticoids was associated with a reduced occurrence of IH (OR 0.566, 95% CI 0.332-0.964) and neonates with IH showed a prolonged total hospital stay compared to controls (69 vs. 57 days, p = 0.0033). Known risk factors for IH were confirmed by our large study cohort and included female gender, low birth weight, preterm birth and multiple gestations (all p < 0.005).ConclusionsExposure to fenoterol during pregnancy does not increase the occurrence of IH. Further studies are needed to explore differences in the risk profiles of different β2-sympathomimetic tocolytic drugs.
Im Titel ist die Zahl "2" tiefer gestellt
Gesehen am 04.11.2019